Genetic manipulation for abiotic stress resistance traits in crops - Esmaeili, Nardana; Shen, Guoxin; Zhang, Hong (Frontiers in Plant Science, 2022)
Abiotic stresses are major limiting factors that pose severe threats to agricultural production. Conventional breeding has significantly improved crop productivity in the last century, but traditional breeding has reached its maximum capacity due to the multigenic nature of abiotic stresses. Alternatively, biotechnological approaches could provide new opportunities for producing crops that can adapt to the fast-changing environment and still produce high yields under severe environmental stress conditions. Many stress-related genes have been identified and manipulated to generate stress-tolerant plants in the past decades, which could lead to further increase in food production in most countries of the world. This review focuses on the recent progress in using transgenic technology and gene editing technology to improve abiotic stress tolerance in plants, and highlights the potential of using genetic engineering to secure food and fiber supply in a world with an increasing population yet decreasing land and water availability for food production and fast-changing climate that will be largely hostile to agriculture.